Effect of Pedagogical Analogical Model on Female First Secondary Scientific Stream Students' Achievement in Molecular Genetics - Alkhawawaldeh, Salem (Jordan Journal of Educational Sciences, 2008)
This study aimed at investigating the effect of the analogical model based on static two-dimensional illustrations (illustrations model) on female first secondary scientific stream students' achievement in molecular genetics, compared with the traditional method. The sample of the study consisted of 54 female first secondary scientific stream students' in two classes of the same high school located in Mafraq city. The experimental group which consisted of 26 students received instruction using the integrated illustration model. Whereas the control group consisted of 28 students used the traditional method. A pretest-post-test control group design utilising the analysis of covariance (two-way ANCOVA) was used to test the hypotheses of the study. The statistical treatment of the data of the study showed the following findings: - There were statistically significant differences in female first secondary scientific stream students' achievement in molecular genetics that can be attributed to instructional method using the illustration model. Those differences were in favor of the students in the experimental group. - There were statistically significant differences in female first secondary scientific stream students' achievement in molecular genetics that can be attributed to formal thinking using the concrete method. Those differences were in favor of formal thinkers. - There is no significant effect in the female first secondary scientific stream students' achievement in molecular genetics that can be attributed to the interaction between the instructional method and formal thinking. Several recommendations were suggested upon the results of the study.